Striptease : the untold history of the girlie show - Shteir, Rachel, 1964- (Oxford University Press, 2004)
The fascinating, untold story of the history of undressing: over fifty years of taking it off. Striptease combined sexual display and parody, cool eros and wisecracking Bacchanalian humor. Striptease could be savage, patriotic, irreverent, vulgar, sophisticated, sentimental, and subversive--sometimes, all at once. In this vital cultural history, Rachel Shteir traces the ribald art from its nineteenth century vaudeville roots, through its long and controversial career, to its decline during the liberated 1960s. The book argues that striptease is an American form of popular entertainment--maybe the most American form of popular entertainment. Based on exhaustive research and filled with rare photographs and period illustrations, Striptease recreates the combustible mixture of license, independence, and sexual curiosity that allowed strippers to thrive for nearly a century. Shteir brings to life striptease's Golden Age, the years between the Jazz Age and the Sexual Revolution, when strippers performed around the country, in burlesque theatres, nightclubs, vaudeville houses, carnivals, fairs, and even in glorious palaces on the Great White Way. Taking us behind the scenes, Rachel Shteir introduces us to a diverse cast of characters that collided on the burlesque stage, from tight-laced political reformers and flamboyant impresarios, to drag queens, shimmy girls, cootch dancers, tit serenaders, and even girls next door, lured into the profession by big-city aspirations.